The Influence of Digital Banking, Motivation, Training and Leadership on Employee Performance - Astarizal, Astarizal; Ngaliman, Ngaliman; Windayati, Diana Titik (Zona Manajerial: Program Studi Manajemen (S1), 2022)
This study aims to determine the factors that influence the dependent variable Y (employee performance). While the independent variables are X1 (digital banking), X2 (motivation), X3 (training) and X4 (leadership) at PT Bank Central Asia Batam Branch. The population is all employees of PT Bank Central Asia Batam Branch as many as 135 employees. The sample was taken using the slovin formula with an e value of 5% so that the sample processed in the study was 100 employees. The data analysis technique is processed using the Statistical Product and Service Solution (SPSS) version 25 program application. The results of the data analysis resulted in a multiple linear regression equation Y = 11.529 + 0.247X1 + 0.464X2 - 0.010X3 + 0.147X4 + e. partially from each independent variable is digital banking of 0.168 > 0.05, motivation of 0.000 < 0.05, training of 0.933 > 0.05 and leadership of 0.181 > 0.05. Partial regression analysis results show that digital banking, training and leadership variables have a positive and insignificant effect on employee performance while motivation has a positive and significant effect on employee performance. The variables X1 (digital banking), X2 (motivation), X3 (training) and X4 (leadership) together contribute to a positive and significant influence on Y (employee performance) with a significance degree (Sig F) of 0.000 on employee performance <0.05.